The Cipp Model in Evaluating the Independent Curriculum: A Study of Islamic Religious Education and Ethics in Muhammadiyah Kleco II Elementary School Kotagede, Yogyakarta - Nurhaliza, Nurhaliza; Munajat, Nur; Rifai, Ikhsan (Kalijaga Journal of Islamic Religious Education, 2025)
Education plays a crucial role in preparing generations to face future challenges, and the curriculum is key to ensuring relevant learning. The Independent Curriculum (Kurikulum Merdeka) is a flexible innovation that adapts to the needs of the 21st century, particularly following the learning loss caused by the COVID-19 pandemic. However, its implementation in elementary schools continues to face challenges, necessitating a comprehensive evaluation. This study applies the Independent Curriculum to fourth-grade Islamic Religious Education and Character Education (PAI and BP) at Muhammadiyah Kleco II Elementary School, Kotagede, the driving school and pilot study. The study used a qualitative approach with the CIPP (Context, Input, Process, Product) model. Data were collected through observation, semi-structured interviews, and documentation, then analyzed using the Huberman and Saldana model. The research subjects consisted of a content standard coordinator teacher, a PAI and BP teacher, and six fourth-grade students. The study lasted six months, with data validity tested through source triangulation, technique triangulation, and method validation. The results showed that the implementation of the Independent Curriculum in PAI and BP was successful, with school support, teacher readiness, and flexible and collaborative learning. Students experienced improvements in character and understanding. However, challenges remained, such as time constraints, lack of parental understanding, and the need for teacher training. These solutions were implemented through time management, teacher competency improvement, intensive communication, and collaboration between teachers.